The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijms24010069
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Drug Synergism between Peptides and Antineoplastic Drugs Paclitaxel, 5-Fluorouracil, and Doxorubicin Using In Silico Approaches

Abstract: Chemotherapy is the main treatment for most early-stage cancers; nevertheless, its efficacy is usually limited by drug resistance, toxicity, and tumor heterogeneity. Cell-penetrating peptides (CPPs) are small peptide sequences that can be used to increase the delivery rate of chemotherapeutic drugs to the tumor site, therefore contributing to overcoming these problems and enhancing the efficacy of chemotherapy. The drug combination is another promising strategy to overcome the aforementioned problems since the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Peptide combinations with PTX and DOX have been shown not to be effective against MCF-7 and PC-3 cancer cells compared to drug treatment. However, as expected in silico, the combination of peptides with 5-FU produced synergistic cytotoxic effects against HT-29 colorectal cancer cells [ 281 ].…”
Section: Calculation Methods In Drug Designmentioning
confidence: 65%
“…Peptide combinations with PTX and DOX have been shown not to be effective against MCF-7 and PC-3 cancer cells compared to drug treatment. However, as expected in silico, the combination of peptides with 5-FU produced synergistic cytotoxic effects against HT-29 colorectal cancer cells [ 281 ].…”
Section: Calculation Methods In Drug Designmentioning
confidence: 65%
“…The overarching goal is to significantly enhance the effectiveness of chemotherapy, while simultaneously mitigating its associated side effects and the potential development of drug resistance [20][21][22]. Previous research from our group has identified the synergistic interactions between various peptides, CPPs, and established chemotherapeutic agents such as paclitaxel (PTX), 5-fluorouracil (5-FU), and clotrimazole (CLZ) by enhancing the delivery of chemotherapeutic agents to different cancer cells [23]. In addition, a different study explored the potent anticancer properties of CPP2-thiazole conjugates.…”
Section: Introductionmentioning
confidence: 99%